PENGEMBANGAN EVALUASI PAI DENGAN TES DIAGNOSTIK - Achmad Rasyid Ridha; Ahmad Suparno Basri; Abdullah Aufa Nadhif (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Islamic Religious Education (IRE) plays a strategic role in shaping students' character, morals, and personality amid the challenges of globalization and external cultural influences. Therefore, IRE should not only target cognitive aspects but also address affective and psychomotor dimensions. Evaluation in IRE learning should go beyond summative assessment and include diagnostic approaches to identify students' learning difficulties in depth. Diagnostic tests serve as essential tools to uncover misconceptions and obstacles students face in understanding religious material, thereby supporting adaptive and responsive learning. Unfortunately, current evaluation practices rarely utilize this approach effectively. In line with the Merdeka Curriculum, which emphasizes formative and diagnostic assessment, the development of diagnostic tests in IRE is urgently needed to realize differentiated learning that aligns with students' conditions and potential.